4
$\begingroup$

A mean-reverting geometric Brownian motion is defined by a system of the equations:

$$dX_t = \mu(X_t, \overline{X}_t) X_t dt + σ X_t dW_t$$ and

$$d\overline{X}_t = λ(\overline{X}_t − X_t)dt \, .$$

Suppose we want to calculate $$f(x,\overline{x},t) = \mathbb{E} \left[V(X_T) \middle\vert \{ X_t = x, \overline{X}_t = \overline{x} \} \right] \, .$$

Write the partial differential equation satisfied by $f$.

$\endgroup$
  • 1
    $\begingroup$ Thanks for down-voting my question -) Don't worry -- I will answer my own question in a few days. $\endgroup$ – wsw Dec 11 '12 at 7:23
5
$\begingroup$

First, let's work out a standard problem, where $$ g(w, t) = \mathbb{E} \left[ V(W_T) \middle \vert W_t = w \right] \, .$$ Integrate both sides from $t$ to $T$: $$ V(W_T) - g(W_t, t) = \int_t^T dg(W_s, s) = \int_t^T \left( \partial_s g \cdot ds + \partial_w g \cdot dW_s + \frac{1}{2} \partial_w^2 g \cdot ds \right) \, . $$ Note that $\mathbb{E}\left[ \int_t^T \partial_w g \, dW_s \right] = 0$ since $dW_s$ is in the future of $W_t = w$. Next, take the expectation on both sides conditional on the filtration $\mathcal{F}_t$: $$ \mathbb{E} \left[ V(W_T) - g(W_t, t) \middle \vert \mathcal{F}_t \right] = \mathbb{E} \left[ \int_t^T \left( \partial_s g + \frac{1}{2} \partial_w^2 g \right) ds \middle \vert \mathcal{F}_t \right] $$

$$ g(W_t, t) - g(W_t, t) = 0 = \mathbb{E} \left[ \int_t^T \left( \partial_s g + \frac{1}{2} \partial_w^2 g \right) ds \middle \vert \mathcal{F}_t \right] \, . $$ We expect the integrand on the right-hand-side to be zero; that is, $$ \partial_t g + \frac{1}{2} \partial_w^2 g = 0 \, , $$ which is the backward PDE for $g(w,t)$.

Next, let's use the same approach for $f(x,\overline{x},t)$. Again, integrate both sides from $t$ to $T$: $$ V(X_T) - f(X_t, \overline{X}_t, t) = \int_t^T df(X_s, \overline{X}_s, s) = \int_t^T \left( \partial_t f \cdot ds + \partial_x f \cdot dX_s + \frac{1}{2} \partial_x^2 f \cdot dX_s^2 + \partial_\overline{x} f \cdot d\overline{X}_s + \frac{1}{2} \partial_\overline{x}^2 f \cdot d\overline{X}_s^2 \right) \, . $$ Note that $ dX_s^2 = \sigma^2 X_s^2 ds + \mathcal{O}(ds^2)$, and $d\overline{X}_s^2 = \lambda^2 \left(X_s - \overline{X}_s \right)^2 ds^2 = \mathcal{O}(ds^2) $.

Take the expectation on both sides conditional on the filtration $\mathcal{F}_t$: $$ \mathbb{E} \left[ V(X_T) - f(X_t, \overline{X}_t, t) \middle \vert \mathcal{F}_t \right] = 0 = \mathbb{E} \left[ \int_t^T \left( \partial_t f + \partial_x f \cdot \mu X_s + \frac{1}{2} \partial_x^2 f \cdot \sigma^2 X_s^2 + \partial_\overline{x} f \cdot \lambda (X_s - \overline{X}_s) \right) ds \middle \vert \mathcal{F}_t \right] \, .$$

Hence the backward PDE is $$ \partial_t f + \partial_x f \cdot \mu X_s + \frac{1}{2} \partial_x^2 f \cdot \sigma^2 X_s^2 + \partial_\overline{x} f \cdot \lambda (X_s - \overline{X}_s) = 0 \, .$$

$\endgroup$
1
$\begingroup$

if $f(x,\bar{x},t) = \mathbb{E}[V(X_T) | \{ X_t = x , \bar{X_t} = \bar{x} \}]$, then let us perform ito's lemma on $V(X_T)$ itself.

$$ dV = \frac{\partial V}{\partial X}dx + \frac{\partial V}{\partial t}dt + \frac{1}{2} \frac{\partial^2 V}{\partial x^2}(dx)^2 $$

We know that $f(x,\bar{x},t) = \mathbb{E}[V(X_T) | \{ X_t = x , \bar{X_t} = \bar{x} \}]$

Therefore, $f(x,\bar{x},t)$ must satisfy the pde $\mathbb{E}[\frac{\partial V}{\partial X}dx + \frac{\partial V}{\partial t}dt + \frac{1}{2} \frac{\partial^2 V}{\partial x^2}(dx)^2 ]$ which looks something like Feynman-Kac

http://en.wikipedia.org/wiki/Feynman%E2%80%93Kac_formula

$\endgroup$
  • 1
    $\begingroup$ I don't think you can write a PDE on $V$ since $V = V(x)$ only. $\endgroup$ – wsw Dec 11 '12 at 19:27

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.